Operational and investigative activities in places of imprisonment: new realities - Єгоров, Сергій Олександрович; Єгоров, С. О.; Егоров, Сергей Александрович; Yehorov, Serhii O.; Щурат, Тарас Григорович; Щурат, Т. Г.; Щурат, Тарас Григорьевич; Shchurat, Taras H.; Поляков, Євген Валентинович; Поляков, Є. В.; Поляков, Евгений Валентинович; Poliakov, Yevhen V.; et al. (Editorial Primmate S. A. S., 2021)
One of the factors influencing the effectiveness of sustainable development of the society is the state of the organization of the fight against crime, which is an integral part of any community. The success of the models of influence on crime chosen by the state depends on: the structure and dynamics of criminal activity in society; the intensity of the processes of self-reproduction of crime; the extent of public involvement in illegal social practices; the impact of criminal structures on economic, and political processes. The purpose of the work is to analyze the nature and structure of operational and investigative activities in places of imprisonment. The research methodology: dialectical method; method of analysis; formal-logical methods; synthesis method; system-structural method; methods of induction and deduction; statistical methods; and method of scientific abstraction. As a result of the study, the authors of the article came to the conclusion that operational and investigative activities in places of imprisonment are specific activities that differ significantly from other areas of operational and investigative activities, and require serious theoretical consideration.

Одним із чинників, які впливають на ефективність перманентного розвитку суспільства є стан організації протидії злочинності, яка є невід’ємною складовою будь-якої спільноти. Від ефективності обраних державою моделей впливу на злочинність залежить: структура та динаміка кримінальної активності у суспільстві; інтенсивність процесів самовідтворення злочинності; масштаби втягнення населення у протиправні соціальні практики; вплив кримінальних структур на економічні та політичні процеси. Метою роботи єздійснення аналізу сутності та структури оперативно-розшукової діяльності у місцях позбавлення волі. Об’єктом дослідження є оперативно-розшукова діяльності у місцях позбавлення волі. Предметом дослідження є суспільні відносини, що виникають в процесі оперативно-розшукової діяльності у місцях позбавлення волі. Методологію дослідження становлять діалектичнийметод; метод аналізу; формально-логічні методи; метод синтезу; системно-структурнийметод; методи індукціїта дедукції; статистичні методи; та методнауковоїабстракції. У результаті проведеного дослідження автори статті дійшли висновку, що оперативно-розшукова діяльності у місцях позбавлення волі є специфічною діяльністю, яка істотно відрізняється від інших напрямків оперативно-розшукової діяльності, і потребує серйозного теоретичного осмислення.
Yehorov S. Operational and investigative activities in places of imprisonment: new realities / S. Yehorov, T. Shchurat, Ye. Polyakov, D. Tsekhan // Amazonia Investiga. – Vol. 10. - Issue 40. – Editorial Primmate S. A. S., 2021. – P. 201-211.
Keywords: criminal punishment; operational and investigative activities; places of imprisonment; operative subdivisions; penitentiary institutions; кримінальне покарання; оперативно-розшукова діяльність; місця позбавлення волі; оперативні підрозділи; установи виконання покарань; Research Subject Categories::LAW/JURISPRUDENCE